Acordos de pesca como instrumento de gestão: estudo de caso nos municípios de Boa Vista do Ramos e Parintins - Amazonas - Aquino, Alzenilson (Instituto Nacional de Pesquisas da Amazônia - INPA, 2018)
World population growth, increased pressure on fishing resources to meet local, national and international market demand, as well as catching fish with better equipped boats and more efficient equipment, led to overfishing, causing conflicts over the resource. The lack of public policies to regulate fishing activities, especially in the Amazon, has caused conflicts between fishermen and residents of communities that live on fish. One of the tools used to mitigate the conflicts was the Fisheries Agreements implemented in the region from the 1995s. This instrument is regulated by Ibama and the State Secretariats of the Environment through Ordinances and Normative Instructions that have as purpose to guarantee the stock and fish production for riverine communities. Fisheries Agreements are considered as dynamic and participatory instruments and should be evaluated annually on the basis of information provided by monitoring. This work aimed to analyze the Fisheries Agreements as a management tool in the State of Amazonas working with a qualitative approach in two municipalities. Data were collected from local fishermen and institutions that participated in the process of drawing up Fisheries Agreements and maintain them. Twenty local fishermen and 11 fishery institutions were interviewed. Documents and documents relating to existing normative instructions were also read and observed. The State of Amazonas has 70 Fisheries Agreements, distributed in 35 municipalities. The municipalities studied, Boa Vista do Ramos and Parintins, have respectively three and one Fisheries Agreements. The Fisheries Agreements analyzed in Boa Vista do Ramos and Parintins are considered positive by fishermen. In addition, they pointed to this instrument as a generator of benefits referring to the recovery of fish stocks, improvement of income of fishermen and promotion of conflict reduction. However, for fishermen and institutions it is the lack of public authority that helps ensure that the Agreements do not function properly leading to loss of natural resources, biodiversity and a decline in fishing activity due to the scarcity of fish in the region.
Keywords: Lago de Várzea; População ribeirinha; Recursos pesqueiros